THE FACTORS INFLUENCING TO ACUTE RESPIRATORY TRACT INFECTIONS IN TODDLERS IN BESU VILLAGE KONAWE REGENCY: ACUTE RESPIRATORY TRACT INFECTIONS - Yanti, Fitri; Buton, La Djabo; Fitri, Fitri (STIKes Mandala Waluya Kendari, 2024)
Background: Acute Respiratory Infection (Acute Respiratory Infection) is the main cause of morbidity and mortality of infectious diseases in the world. This study aims to determine the factors associated with the incidence of Acute Respiratory Infection in toddlers in Besu Village, Morosi District, Konawe Regency. The type of research used is quantitative research with a Cross-Sectional Study design. Methods: The population in this study was 52 toddlers, with a sample of 47 people. The sampling technique used simple random sampling. Data analysis used the Chi Square test. Results: This study obtained variables of maternal knowledge (X2 count = 9.312; Phi = 0.489), exposure to cigarette smoke (X2 count = 6.365; Phi = 0.415), residential density (X2 count = 2.888), ventilation ( X2 count = 8.263; Phi = 0.462), and distance from home to the highway (X2 count = 6.057; Phi = 0.404). Conclusion: there is a relationship between maternal knowledge, exposure to cigarette smoke, ventilation, and the distance of the house to the highway with the occurrence of Acute Respiratory Infection in Besu Village and there is no relationship between residential density and the occurrence of Acute Respiratory Infection in Besu Village, Morosi District, Konawe Regency. Suggestions for the Morosi Health Center to provide intensive counseling about healthy homes and child-friendly areas free of cigarette smoke.